GAMBARAN PEMAKAIAN DIAPERS SEKALI PAKAI PADA ANAK USIA PRASEKOLAH - Ns. Lita (LPPM Universitas Muhammadiyah Riau, 2017)
This study is to identify the picture of the use of disposable diapers in children aged prasekolah. Desain used in thisstudy is a simple descriptive with cross sectional approach. A sample of 57 people at Tk Az-Zuhra village Pekanbaru Simpang Tiga. The analysis used is a univariate analysis with frequency distribution. The results of this study found that the average age is 30.56 years old mother, the mother's last majority of education is higher education (50.9%), most of the work mothers are housewives (43.9%), the economic status of many with moderate status (54.4%). Most were female gender (57.9%), the average age was 48.14 months and age started using diapers 7.84 a month, and impaired skin as much as 36.8%. From the research results are expected to improve the mother's knowledge about the impact of using diapers to preschoolers who are at Tk Az-Zuhra village Pekanbaru Simpang Tiga.